https://www.anbarjvs.edu.iq/wp-content/uploads/2021/06/1.pdf - Kifah Odhaib; Measem Alallawee; Zainab AL-Mousawi (مجلة الانبار للعلوم البيطرية, 2021)
The purpose of this review is to summarize the effectiveness, modes of action and commercial application of herbal plants and their derivatives as growth promoters for animal. As described in literature, the increase in the growth of farming prices and feed costs for small ruminant in general, led to increases difficulties in production of livestock. To dissolve this issue, several studies concentrated on new alternative of feed resource, but others have tried to enrich milk products and meat by rising polyphenol compounds content to their by introductions of herbal plants in sheep and goat feed. Currently, consumers demand safety and the quality of feeding. Since antibiotics can be leave residues in ruminant tissues, that could induce subsequent emergence of resistant strains of microorganisms capable of endangering the health of livestock and human. This scenario has given the impetus to explore alternatives to antibiotics in animal nutrition. Consequently, as replacement for the synthetic growth promoter’s antibiotics, natural products like herbs and spice as natural feed additives come to the attention to enhance physiological functions. So, the use of feeds containing bioactive compounds such as thymol, flavonoids, saponins, limonene, thymoquinone, essential oils and others which concentrated in different parts, such as leaves, roots and seeds that can be used for these purpose in animal feed and responsible for the healthy animal product. Furthermore, one of the hot points in the advanced research is the stability of animal product against the oxidative deterioration process that limits the shelf life.